2005
DOI: 10.1182/blood-2003-11-3900
|View full text |Cite
|
Sign up to set email alerts
|

Functional defect of regulatory CD4+CD25+ T cells in the thymus of patients with autoimmune myasthenia gravis

Abstract: Thymus-derived CD4 IntroductionThe development of autoimmune diseases involves a breakdown in the mechanisms that control self-reactive lymphocytes. The primary mechanism that generally maintains self-tolerance is thymic deletion of autoreactive T cells with high affinity for self-antigens. However, this mechanism is not perfect and autoreactive T cells do escape to the periphery. Recent data suggest that in addition to the mechanisms of clonal deletion and anergy, regulatory T (Treg) cells play a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
283
2
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 379 publications
(299 citation statements)
references
References 44 publications
11
283
2
3
Order By: Relevance
“…Ó 2007 Blackwell Publishing Ltd, Immunology, 121, [15][16][17][18][19][20][21][22][23][24][25][26][27][28] that over-expressed Foxp3 had increased numbers of Tregs in the periphery. [8][9][10] Dysregulation of Treg function has been implicated as an important event in the development of autoimmunity in animal models and in spontaneous autoimmune diseases in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ó 2007 Blackwell Publishing Ltd, Immunology, 121, [15][16][17][18][19][20][21][22][23][24][25][26][27][28] that over-expressed Foxp3 had increased numbers of Tregs in the periphery. [8][9][10] Dysregulation of Treg function has been implicated as an important event in the development of autoimmunity in animal models and in spontaneous autoimmune diseases in humans.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] Defects in Treg function have also been observed in other autoimmune diseases, including rheumatoid arthritis, myasthenia gravis, multiple sclerosis and autoimmune polyglandular syndrome type II. [20][21][22][23] In addition, reversal of compromised Treg function has been demonstrated in humans with rheumatoid arthritis who experienced clinical improvement following anti-tumour necrosis factor-a therapy. 20 In light of these observations, we evaluated the frequency and function of Tregs in our NOD mouse colony.…”
Section: Discussionmentioning
confidence: 99%
“…2,7 The various Treg cells have key roles in maintaining self-tolerance and modulating the allergic and autoimmune responses, while controlling autoreactive T cells. [8][9][10][11] Several studies have reported a deficiency in the number of Treg and/or function in autoimmune disease patients, 12,13 namely in systemic lupus erythematous, 14 rheumatoid arthritis, 15 multiple sclerosis, 16 autoimmune polyglandular syndrome II, 17 myasthenia gravis 18 and type I diabetes. 19 However, results concerning the number of circulating Treg cells and their suppressive function have been contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…The development and function of T R cells is controlled by Foxp3 (refs 1, 2), a lack of which results in loss of T R cells and massive multi-organ autoimmunity in scurfy mice and IPEX (immune dysregulation, polyendocrinopathy, enteropathy, X-linked) patients 3,4 . It is generally thought that, through a binary mechanism, Foxp3 expression serves as an on-and-off switch to regulate positively the physiology of T R cells; however, emerging evidence associates decreased Foxp3 expression in T R cells with various immune disorders [5][6][7] . We hypothesized that Foxp3 regulates T R cell development and function in a dose-dependent, nonbinary manner, and that decreased Foxp3 expression can cause immune disease.…”
mentioning
confidence: 99%